2015
DOI: 10.1017/s0022215115000092
|View full text |Cite
|
Sign up to set email alerts
|

Routine non-thyroid head and neck cytology in a large UK centre: clinical utility and pitfalls

Abstract: Head and neck cytology is a robust technique at our institution, although there are certain problem areas. There is room for improvement in the technical quality of fine needle aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…When FNAB is combined with ultrasound guidance, FNAB demonstrates a diagnostic accuracy between 95% and 100% 2,4,6,7,9‐12 . While overall diagnostic accuracy is well documented, less is known about node characteristics impacting the technique's sensitivity for identification of metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…When FNAB is combined with ultrasound guidance, FNAB demonstrates a diagnostic accuracy between 95% and 100% 2,4,6,7,9‐12 . While overall diagnostic accuracy is well documented, less is known about node characteristics impacting the technique's sensitivity for identification of metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Firat et al 21 identified 1 benign branchial cyst that was reported as highly suspicious of carcinoma. Kaye et al 22 reported that of 22 lesions confirmed to be a benign branchial cyst, 1 was suspicious of squamous cell carcinoma. Kadhim et al 23 reported that of 34 patients with a cytology aspirate from a benign branchial cleft cyst, 1 was reported as cytologically suspicious of squamous cell carcinoma.…”
Section: Lateral Neck Cystsmentioning
confidence: 99%